WESTERN UKRAINIAN AND POLISH PROSE IN THE TWENTIES–THIRTIES: ETHNOCENTRIC AND POLYCENTRIC ASPECTS - Maftyn, Natalia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The article deals with the main trends in the development of Polish and Western Ukrainian prose of<a href="https://context.reverso.net/%D0%BF%D0%B5%D1%80%D0%B5%D0%B2%D0%BE%D0%B4/%D0%B0%D0%BD%D0%B3%D0%BB%D0%B8%D0%B9%D1%81%D0%BA%D0%B8%D0%B9-%D1%83%D0%BA%D1%80%D0%B0%D0%B8%D0%BD%D1%81%D0%BA%D0%B8%D0%B9/twenty+interwar+years"> interwar years of the last century, caused by the connection of the author's practice with a certain historical experience. Here the influence of pan-European artistic factors on the situation in the prose of the two literatures, as well as the determinism of the popularity of certain ideological and thematic, genre and style spectra by different political situation.